Retroperitoneoscopic adrenalectomy may be superior to laparoscopic transperitoneal adrenalectomy in terms of costs and profit: a retrospective pair-matched cohort analysis - Fischer, Andreas; Schöffski, Oliver; Nießen, Anna; Hamm, Alexander; Langan, Ewan A.; Büchler, Markus W.; Billmann, Franck (Surgical Endoscopy, 2023)
Background: A direct comparison of the cost–benefit analysis of retroperitoneoscopic adrenalectomy (RPA) versus the minimally invasive transperitoneal access (LTA) approach is currently lacking. We hypothesized that RPA is more cost effective than LTA; promising significant savings for the healthcare system in an era of ever more limited resources. Methods: We performed a monocentric retrospective observational cohort study based on data from our Endocrine Surgery Registry. Patients who were operated upon between 2019 and 2022 were included. After pair-matching, both cohorts (RPA vs. LTA) were compared for perioperative variables and treatment costs (process cost calculation), revenue and profit. Results: Two homogenous cohorts of 43 patients each (RPA vs. LTA) were identified following matching. Patient characteristics between the cohorts were comparable. In terms of both treatment-associated costs and profit, the RPA procedure was superior to LTA (costs: US5789.99 for RPA vs. US6617.75 for LTA, P = 0.043; profit: US1235.59 for RPA vs. US653.33 for LTA, P = 0.027). The duration of inpatient treatment and comorbidities significantly influenced the cost of treatment and the overall profit. Conclusions: RPA appears not only to offer benefits over LTA in terms of perioperative morbidity and length of hospital stay, but also has a superior financial cost/benefit profile. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-09-08
Keywords: Adrenalectomy; Benefits and costs; Minimally invasive surgical procedures; Multivariate analysis